2015
DOI: 10.1177/0143624414566242
|View full text |Cite
|
Sign up to set email alerts
|

Cooling the UK housing stock post-2050s

Abstract: This paper investigates the risk of projected post-2050s overheating in existing, retrofitted and new-build dwellings in the UK. As previous research has shown, passive measures may not be sufficient in mitigating overheating risk. Therefore, mechanical cooling technologies that may be deployed to 'adapt' to a warming climate are tested for energy and CO 2 implications. For retrofits, heating demand is projected to remain dominant, whereas in post-2016 new-build, greater cooling system efficiency will be impor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
24
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 22 publications
1
24
0
Order By: Relevance
“…(ii) modelling studies (de Wilde & Coley, 2012;Gul et al, 2015;Gupta, Gregg, & Williams, 2015;Gupta & Gregg, 2012;Holmes & Hacker, 2007;McLeod, Hopfe, & Kwan, 2013;Oikonomou et al, 2012;S. M. Porritt, Cropper, Shao, & Goodier, 2012;S.…”
Section: Introductionmentioning
confidence: 99%
“…(ii) modelling studies (de Wilde & Coley, 2012;Gul et al, 2015;Gupta, Gregg, & Williams, 2015;Gupta & Gregg, 2012;Holmes & Hacker, 2007;McLeod, Hopfe, & Kwan, 2013;Oikonomou et al, 2012;S. M. Porritt, Cropper, Shao, & Goodier, 2012;S.…”
Section: Introductionmentioning
confidence: 99%
“…This is most effective when using light coloured temporary shading as it is the best solar gain reflector 6 , while also maximising winter solar gains. In the case study, internal shading indicated a significant reduction to overheating frequencies in both the 2050s and 2080s HiES scenarios.…”
Section: " ' (mentioning
confidence: 99%
“…[6][7][8][9][10] Currently, 20% of homes in England might already experience overheating in summer and this is likely to increase in a warming climate. 11 In southern European countries the proportion of occupants experiencing discomfort in their homes during summer can be nearly as high as 50%.…”
mentioning
confidence: 99%
See 2 more Smart Citations